Implementation of Traumatic Healing for Earthquake Victim Children through Fun Outbound Activities: Pelaksanaan Traumatic Healing bagi Anak Korban Gempa melalui Kegiatan Fun Outbond - Adji, Sandra Sukmaning; Sausan, Inas; Suciana, Dola; Masbukhin, Faizal Akhmad Adi; Fahimah, Ayu (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
On November 21, 2022, Cianjur, West Java, experienced an earthquake with a magnitude of Mw 5.6, followed by 140 aftershocks until November 22, 2022. The earthquake resulted in loss of life, injuries, and infrastructure damage. The damaged school conditions due to the earthquake affected the learning environment for children, subsequently influencing their motivation and academic performance. Additionally, the psychological impact on survivors, particularly children, included anxiety, depression, and post-traumatic stress disorder (PTSD). This article discusses the importance of psychological recovery for children after a disaster, particularly earthquakes, using fun outbound activities as a method of traumatic healing. Fun outbound comprises outdoor activities involving games, physical challenges, and group cooperation. The study indicates that fun outbound can assist children in overcoming fear and trauma, boost self-confidence, and develop social skills. The research was conducted at SDN Sukamaju 1 Cugenang, one of the schools significantly affected by the earthquake. Through tangram puzzle games and synchronized cooperation, students experienced joy and enthusiasm, with over 50% of them reporting relief from fear and trauma. Evaluation results demonstrate the effectiveness of fun outbound in supporting the psychological recovery of children after a disaster. In conclusion, the fun outbound method can be an effective tool in helping earthquake-affected children overcome trauma, enhance self-confidence, and build social skills, creating a positive and enjoyable environment for children in challenging post-earthquake situations.